# Solve for x: (1 – i) x + (1 + i) y = 1 – 3i.

we have, (1 – i) x + (1 + i) y = 1 – 3i

x-ix+y+iy = 1-3i

(x+y)+i(-x+y) = 1-3i

On equating the real and imaginary coefficients we get,

x+y = 1 (i) and –x+y = -3 (ii)

From (i) we get

x = 1-y

substituting the value of x in (ii), we get

-(1-y)+y=-3

-1+y+y = -3

2y = -3+1

y = -1

x=1-y = 1-(-1)=2

Hence, x=2 and y = -1

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Polar & Euler Form of Complex Numbers on Argand Plane32 mins
Interactive Quiz Time - Polar & Euler Form of complex number58 mins
Practice session | Argument of complex numbers61 mins
Modulus & Conjugate of Complex Number | Ready for a Quiz?48 mins
Interactive Quiz on Quadratic Equations73 mins
Special Quiz on Argument of complex numbers56 mins
Polar & Euler Form of Complex Number on Argand Plane58 mins
Questions on Modulus & Conjugate of Complex Number62 mins
Questions Based on Polar & Euler Form of Complex Number63 mins
Interactive Quiz on Quadratic Equations-0252 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses